The Effect of Organizational Citizenship Behavior and Employee Psychological Capital on Employee Performance at Bank Sumut with Job Satisfaction as a Moderating Variable - Hutapea, Michael; Dalimunthe, Ritha F; Sirozujilam, Sirozujilam (PT FORMOSA CENDEKIA GLOBAL, 2025)
In an increasingly dynamic work environment, employees' ability to voluntarily contribute through Organizational Citizenship Behavior (OCB) and possess high Psychological Capital, such as optimism, hope, resilience, and self-efficacy, is considered a critical factor influencing performance. Moreover, job satisfaction is often regarded as a key element that strengthens the relationship between these variables and performance. This study aims to analyze the influence of Organizational Citizenship Behavior (OCB) and Psychological Capital on employee performance at Bank Sumut, with job satisfaction as a moderating variable. A quantitative approach was employed in this study. The sample consisted of 83 employees out of 473 employees at Bank Sumut, selected using a simple random sampling technique. Data analysis was conducted using Structural Equation Modeling (SEM). The study's findings show that psychological capital and organizational citizenship behavior (OCB) both have a positive impact on employee performance. Job satisfaction also has a positive impact on employee performance, while psychological capital has a stronger effect on Bank Sumut employees' performance thanks to job satisfaction.